Transformational leadership and organisational Performance in private healthcare. A case study of selected private facilities. - Mangwende, M (BUSE, 2022)
Transformational leadership is about encouraging, inspiring, and motivating the workforce in ways that creates meaningful change. This concept has become more important than ever especially in the fourth industrial revolution where organisations are undertaking continuous change. Owing to this, several academics and practitioners have focused on transformational leadership as a research area. However, studies on transformational leadership are largely western context based. In fact, little is known about this concept in the global south. For this reason, the primary goal of this research was to determine how the private healthcare industry's organisational performance was impacted by the four transformational leadership from a Zimbabwean perspective. The researcher employed the deductive method, whereby operational hypotheses describing the relationships between the variables were established and stated. The questionnaires were tested quantitatively in order to produce credible results. Participants were chosen from among the private healthcare facilities in Harare using stratified sampling. 140 respondents returned completed surveys that were used for data analysis after 160 questionnaires were issued to respondents. A 5-point Likert scale was used to measure each scale in the questionnaire. SPSS was used to test hypotheses. The findings revealed that all the four transformational leadership dimensions (inspirational motivation, individualised consideration, intellectual stimulation, and idealised influence) had a significant positive impact on the performance of private healthcare organisations. It is advised that private healthcare facility leadership recognise the impact of the four transformational leadership dimensions on organisational performance, which will ultimately result in the accomplishment of the desired goals and objectives. Additional research should examine how transformational leadership affects organisational performance in other industries in Zimbabwe, like mining and agriculture.
Keywords: transformational; leadership; private healthcare; healthcare; organisational performance